Edukasi dan Penapisan Penyakit Diabetes Melitus Tipe 2 pada Kelompok Lanjut Usia di Gereja Katolik St. Fransiskus Asisi - Alfianto Martin; Alexander Halim Santoso; Triyana Sari; Giovanno Sebastian Yogie; Bruce Edbert; Daniel Goh; Valentino Gilbert Lumintang (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The aim of education and screening for type 2 diabetes mellitus in the elderly group is to provide early detection of type 2 diabetes mellitus and increase knowledge of type 2 diabetes mellitus using seminars, workshops, counseling, and leaflet media. This activity involves checking blood sugar levels as a screening for type 2 diabetes mellitus and providing education regarding signs and symptoms, risk factors, treatment, and complications that occur in type 2 diabetes mellitus. This activity is important to increase insight and create behavior that is willing to carry out self-care so that complications of type 2 diabetes mellitus can be avoided.